Pengaruh Kinerja Keuangan Terhadap Keberlangsungan UMKM di Kabupaten Nagan Raya - Nurhayati Nurhayati; Lilis Marlina; Dewi Sartika; Rimal Mahdani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effect of financial performance on the sustainability of MSMEs in Nagan Raya Regency. MSMEs play an important role in the economy of Indonesia and Aceh; however, they still face major challenges in financial management and financial literacy. This condition is also found in Nagan Raya Regency. Therefore, this study analyzes the influence of financial performance on the sustainability of MSMEs in Nagan Raya Regency. The research employs a quantitative method. The sample consists of 99 MSME actors in Nagan Raya Regency. Data analysis techniques include instrument testing such as validity and reliability tests, simple linear regression analysis, normality testing, hypothesis testing using the t-test, and the coefficient of determination test. The results show that financial performance has a significant effect on the sustainability of MSMEs in Nagan Raya Regency. The positive regression coefficient is 0.722, with a calculated t-value of 8.587, which is greater than the t-table value (1,984), and a significance level of 0.000 (< 0.05). The t-test results further confirm that financial performance partially has a significant effect on MSME sustainability. Thus, it can be concluded that MSMEs with good financial management tend to be more sustainable and capable of long-term growth.